Enhanced optical activity 12 d before X-ray activity, and a 4 d X-ray delay during outburst rise, in a low-mass X-ray binary. Issue 3 (26th August 2020) - Goodwin, A J; Russell, D M; Galloway, D K; Baglio, M C; Parikh, A S; Buckley, D A H; Homan, J; Bramich, D M; in't Zand, J J M; Heinke, C O; Kotze, E J; de Martino, D; et al.
ABSTRACT: X-ray transients, such as accreting neutron stars, periodically undergo outbursts, thought to be caused by a thermal-viscous instability in the accretion disc. Usually outbursts of accreting neutron stars are identified when the accretion disc has undergone an instability, and the persistent X-ray flux has risen to a threshold detectable by all sky monitors on X-ray space observatories. Here, we present the earliest known combined optical, UV, and X-ray monitoring observations of the outburst onset of an accreting neutron star low-mass X-ray binary (LMXB) system. We observed a significant, continuing increase in the optical i ′ -band magnitude starting on July 25, 12 d before the first X-ray detection with Swift /XRT and NICER (August 6), during the onset of the 2019 outburst of SAX J1808.4−3658. We also observed a 4 d optical to X-ray rise delay, and a 2 d UV to X-ray delay, at the onset of the outburst. We present the multiwavelength observations that were obtained, discussing the theory of outbursts in X-ray transients, including the disc instability model, and the implications of the delay. This work is an important confirmation of the delay in optical to X-ray emission during the onset of outbursts in LMXBs, which has only previously been measured with less sensitive all sky monitors. We find observational evidence that the outburst is triggered by ionization of hydrogen in the disc.